PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN PADA OBJEK WISATA RUMAH GADANG MANDE RUBIAH PESISIR SELATAN - Monalisa Monalisa; Rose Rahmidani (Universitas Negeri Padang, 2019)
the purpose of this research is to know the influence of product, promotion, place,physical evidence, employee, process, productivity and quality to decision of tourist visiting at Rumah Gadang Mande Rubiah tourist object. This type of research is causative. The population in this study is all tourists who visit the tourism object that is Pesisir Selatan. The number of research samples was determined based on Cochran formula of 100 people and was chosen by using accidental sampling technique. The data that are used are the primary obtained through the distribusion of questionnaires to selected tourists. The analytical method used is descriptive and quantitative analysis through path analysis. The results of this study indicate objek: 1) The product has significant influence on the tourist visiting decision on Rumah Gadang Mande Rubiah tourism object, 2) Promotion has significant influence on the tourist visiting decision on Rumah Gadang Mande Rubiah tourism object, 3) Place has significant influence the tourist visiting decision at Rumah Gadang Mande Rubiah tourism object, 4) physical evidence Place has no significant effect on the tourist visiting decision at Rumah Gadang Mande Rubiah tourist object, 5) Employees has significant influence on the tourist visiting decision on Rumah Gadang Mande Rubiah tourism object, 6) Process has no significant effect on the tourist visiting decision at Rumah Gadang Mande Rubiah tourist object, 7) Productivity and quality significantly influence the decision of tourists visiting the Rumah Gadang Mande Rubiah tourist object.Keywords: Visiting Devisiting, Product, Promotion, Place, Physical Evidence, Employee, Process, Productivity and Quality.